2009
DOI: 10.1007/s12546-008-9006-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of family caps on the subsequent fertility decisions of never-married mothers

Abstract: Family caps seek to reduce fertility among welfare recipients by denying additional cash assistance to recipients that have children while on welfare. A necessary condition for family caps to be an effective policy tool is that welfare recipients respond to financial incentives in making decisions that affect subsequent fertility outcomes. In this paper I use data from the 2001 panel of the Survey of Income and Program Participation (SIPP) to examine whether welfare mothers respond to the incentive provided by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…The findings in rows (1) and (2) of Table 3 are consistent with Horvath-Rose and Peters (2001), Mach (2001), Wallace (2002), and Sabia (2006). However, they are not consistent with other studies that have found no impact of the family cap when restricting their samples to poor, low-educated, unmarried women and differentiating treatment and control groups by parity (Kearney 2004;Joyce et al 2004a, b).…”
Section: The Family Cap and Nonmarital Childbearing 129supporting
confidence: 47%
“…The findings in rows (1) and (2) of Table 3 are consistent with Horvath-Rose and Peters (2001), Mach (2001), Wallace (2002), and Sabia (2006). However, they are not consistent with other studies that have found no impact of the family cap when restricting their samples to poor, low-educated, unmarried women and differentiating treatment and control groups by parity (Kearney 2004;Joyce et al 2004a, b).…”
Section: The Family Cap and Nonmarital Childbearing 129supporting
confidence: 47%
“…For example, during the 1990s, 35 states proposed financial reimbursements for women on welfare who were implanted with a long-term birth control method, Norplant (Thomas 1998). Currently, 23 states have implemented family caps for welfare recipients, which limit or eliminate the incremental cash assistance associated with additional family members; supporters have argued (erroneously) that family caps incentivize women on welfare to limit their fertility (Wallace 2009). Economically disadvantaged women often internalize beliefs about fertility control and social problems as well.…”
Section: Introductionmentioning
confidence: 99%
“…6 6. A large body of studies on TANF use the SIPP data set, and many of these drop the five states from their analysis (see Bavier 2002;Baltagi and Yen 2014;Herbst 2010;Mazzolari and Ragusa 2012;Ratcliffe et al 2008;Shaefer, Grogan, and Pollack 2011;Wallace 2009). For all analyses, I use individual weight, which is measured at the last wave during the panel.…”
Section: A Data: Survey Of Income and Program Participationmentioning
confidence: 99%
“…A large body of studies on TANF use the SIPP data set, and many of these drop the five states from their analysis (see Bavier ; Baltagi and Yen ; Herbst ; Mazzolari and Ragusa ; Ratcliffe et al ; Shaefer, Grogan, and Pollack ; Wallace ).…”
mentioning
confidence: 99%